Modulation of obesity-induced inflammation by dietary fats: mechanisms and clinical evidence - Teng, Kim-Tiu (BioMed Central, 2014)
Obesity plays a pivotal role in the development of low-grade inflammation. Dietary fatty acids are important modulators of inflammatory responses. Saturated fatty acids (SFA) and n-6 polyunsaturated fatty acids (PUFA) have been reported to exert pro-inflammatory effects. n-3 PUFA in particular, possess anti-inflammatory properties. Numerous clinical studies have been conducted over decades to investigate the impact of dietary fatty acids on inflammatory response in obese individuals, however the findings remained uncertain. High fat meals have been reported to increase pro-inflammatory responses, however there is limited evidence to support the role of individual dietary fatty acids in a postprandial state. Evidence in chronic studies is contradictory, the effects of individual dietary fatty acids deserves further attention. Weight loss rather than n-3 PUFA supplementation may play a more prominent role in alleviating low grade inflammation. In this context, the present review provides an update on the mechanistic insight and the influence of dietary fats on low grade inflammation, based on clinical evidence from acute and chronic clinical studies in obese and overweight individuals.